Efficient transport system of cultivated mushroom mycelium enables its derived carbon with high performance electrochemical desalination capability. (30th August 2022) - Zhao, Chen; Wang, Qin; Chang, Shaozhong; Zhang, Shuo; Li, Zhonghua; Shen, Zihan; Jin, Xin; Xiao, Han; Zhang, Huigang
Abstract: Capacitive deionization (CDI) is regarded as a promising desalination technology because of its high efficiency and low energy consumption. Electrode materials with high surface area, abundant active sites, and interconnected pore structure are the key to enhancing the electrochemical performance of CDI devices. Here, we selectively cultivated mushroom mycelia as the precursor to fabricate a hierarchically porous carbon electrode that consists of interwoven and hollow filaments for the CDI. By using the high-efficiency transport system of mycelia that natural evolution endows with, the resultant mycelia-derived carbon (MDC) exhibits a high surface area of 3603 m 2 g −1 and delivers a high capacity of 260 F g −1 . The assembled CDI devices could realize a superior salt removal capacity of 24.17 mg g −1 . Efficient transport system of mycelia enables MDC to rapidly remove salts from solution with an extremely short characterization time. Such a high-efficiency CDI electrode could be attributed to the use of naturally-optimized transport system, high surface area, and heteroatomic surface. In contrast with artificial chemical synthesis, biologic cultivation offers some higher-order structures that conventional technologies would not easily achieve. This work provides an alternative approach to improving the transport of hierarchical CDI electrodes from living things. Graphical abstract: Image 1 Highlights: High-efficiency transport network of mycelia was used to synthesize electrode materials for capacitive deionization. Higher-order structures of mycelia enables a high specific surface area of 3603 m 2 g −1 and capacitance of 260 F g −1 . The capacitive deionization devices could realize a high salt adsorption capacity of 24.17 mg g −1 and rapid kinetics.